Input on the Measurement and Comprehension of CO2 Solubility in Molten Alkali Carbonates in View of Its Valorization. Issue 6 (18th March 2020) - Meléndez-Ceballos, A.; Gürbüz, E.; Brouzgou, A.; Albin, V.; Ringuedé, A.; Lair, V.; Cassir, M.
Abstract : As the capture and valorization of CO2 in molten carbonates is nowadays becoming a strategic energy topic, the need of accurate solubility measurements of such molecule is becoming compulsory. This study provides a new set of reliable CO2 solubility values, determined by a a carefully adapted manometric setup, in Li2 CO3 -K2 CO3 (62:38 mol%), Li2 CO3 -Na2 CO3 (52:48 mol%), Li2 CO3 -Na2 CO3 -K2 CO3 (43.5:31.5:25.0 mol%) and Na2 CO3 -K2 CO3 (56:44 mol%) carbonate eutectics in an overall range of temperatures from 450 to 850 °C. High solubility values are obtained for Li-K and Li-Na eutectics, respectively 1.7 × 10 −1 and 1.1 × 10 −1 mol atm −1 l −1 at 650 °C. It is shown that CO2 solubility increases with the temperature for most of the eutectic mixtures. Another important trend is that the Li content significantly increases the solubility.